2016
DOI: 10.1038/srep20105
|View full text |Cite
|
Sign up to set email alerts
|

Phenanthrene exposure induces cardiac hypertrophy via reducing miR-133a expression by DNA methylation

Abstract: Growing evidence indicates that there is an emerging link between environmental pollution and cardiac hypertrophy, while the mechanism is unclear. The objective of this study was to examine whether phenanthrene (Phe) could cause cardiac hypertrophy, and elucidate the molecular mechanisms involved. We found that: 1) Phe exposure increased the heart weight and cardiomyocyte size of rats; 2) Phe exposure led to enlarged cell size, and increased protein synthesis in H9C2 cells; 3) Phe exposure induced important ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 54 publications
2
42
0
1
Order By: Relevance
“…Phenanthrene is a major constituent of environmental PAHs and has been reported to be a significant component of DE (49), which suggests that PAHs, including phenanthrene, may possibly contribute to our observed effects on heart failure and DNA methylation. Although we observed in utero DE exposure to result in altered miR133a-2 expression in a manner that was similar to that reported previously (48), our observed DNA methylation results of hypomethylation of the first exon are in contrast and perhaps suggests a unique epigenetic mechanism of action in in utero DE-induced adult susceptibility to heart failure.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Phenanthrene is a major constituent of environmental PAHs and has been reported to be a significant component of DE (49), which suggests that PAHs, including phenanthrene, may possibly contribute to our observed effects on heart failure and DNA methylation. Although we observed in utero DE exposure to result in altered miR133a-2 expression in a manner that was similar to that reported previously (48), our observed DNA methylation results of hypomethylation of the first exon are in contrast and perhaps suggests a unique epigenetic mechanism of action in in utero DE-induced adult susceptibility to heart failure.…”
Section: Discussionsupporting
confidence: 90%
“…The effect of environmental toxicant exposure on cardiac hypertrophy via regulation of miR133a expression and DNA methylation has been previously reported (48). Exposure to the PAH, phenanthrene, causes cardiac and myocyte hypertrophy in both in vivo and in vitro models.…”
Section: Discussionmentioning
confidence: 92%
“…J Physiol 598.2 2016). Furthermore, DNA hypermethylation, another intracellular effect observed upon Phe exposure (Liu et al 2013) has been implicated in the down-regulation of microRNA-133a, leading to increased expression of its target genes such as CdC42 and RhoA (involved in hypertrophic growth response) (Huang et al 2016). In zebrafish, Zhang et al (2013) showed that Phe exposure increased matrix metalloproteinase-9 (MMP-9) expression and activity.…”
Section: Figure 4 Pah and Ec Coupling In Cardiac Myocytesmentioning
confidence: 99%
“…Cellular hypertrophy has been observed in H9C2 rat cardiomyoblasts with low Phe exposure, and in excised rat hearts where Phe increased expression of atrial natriuretic protein (ANP), brain natriuretic protein (BNP), and c‐Myc hypertrophic markers (Huang et al . ). Furthermore, DNA hypermethylation, another intracellular effect observed upon Phe exposure (Liu et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation